The African Dimension of the Oxford English Dictionary - Weiner, Edmund Simon Christopher (Lexikos, 1997)
African languages have contributed and continue to contribute a great many vocabulary items to English, both directly and via the intermediary of other non-African languages. The OED Additions Series contains 63 words of African origin, most of which have come into the language during the last years. The second edition of the OED contains about 275 words of African origin, drawn from 30 languages. The treatment of these words is somewhat uneven, owing to two factors: the unavailability to the editors of relevant information at the time of compilation of OED1; and supremacist attitudes, which caused entries for words of this kind to be shorter and less detailed, and affected their definition and description. In the third edition of the OED, words of all kinds should receive the same degree of attention, which implies that data collection from the reading of primary sources should include all varieties of World English; description and definition should be undertaken from a neutral standpoint; and etymological research and documentation must be as full as is practicable. All items of African origin will be sent to linguistic specialists (the bulk of this work has been done in the DSAE for items of South African origin). The checking of other etymologies will bring to light items whose African origin was not previously indicated (for example, borrowings from Brazilian Portuguese). In a sample from the letter M, there has been a gain in the numbers of African etymologies and the accuracy of treatment. Loanwords of all origins will be given as much attention as our resources allow, but there may be more ground to make up in the African sector of the lexicon. Keywords: african languages, english language, oxford english dictionary, oed additions series, lexicographical documentation, definition, etymology, loanwords, supremacist attitude, third edition of the oed, reading programme, dictionary of south african english on historical principles